Petrochemical waste characterization and management at Pars Special Economic Energy Zone in the south of Iran. Issue 2 (February 2021) - Ghazizade, Mahdi Jalili; Koulivand, Habib; Safari, Edwin; Heidari, Leila
Industrial waste management generated by different petrochemical complexes at Pars Special Economic Energy Zone, located in the south of Iran, was investigated. All 10 active petrochemical complexes were visited and generated wastes were identified by a checklist. Petrochemical plants were classified regarding feeds, process, and products and nine representative wastes were sampled. Physicochemical characteristics were analyzed and appropriate management approaches were proposed according to the literature review and the results of waste characterization. The generated wastes were classified as hazardous and non-hazardous according to the Basel Convention and Environmental Protection Agency lists of waste classification. Also, the concentrations of organic compounds and heavy metals were measured to classify wastes characteristically. Comparing concentrations of the most important heavy metals in sampled wastes illustrated that sandblast with Cu concentration of 4295 mg kg –1, spent activated carbon with Hg concentration of 127 mg kg –1, and spent catalyst with 25% Ni content can be categorized as hazardous wastes, due to the exceeding Total Threshold Limit Concentration levels. Based on laboratory results, all industrial waste generated in the petrochemical complexes were categorized into three groups, namely Organic Waste with High Calorific Value, Non-organic Recyclable Waste, and Non-organic Non-recyclable Waste. Finally, management approaches, including material recycling, energy recovery (through incineration), and landfilling, were proposed and a conceptual model was suggested in order to show different routes and final destination for each kind of waste generated in all similar petrochemical complexes.